MUTED GROUP THEORY ANOMALIES IN ONLINE GENDER-BASED VIOLENCE EXPERIENCED BY WOMEN JOURNALISTS - Retno Manuhoro Setyowati; Errika Dwi Setya Watie (Journal of Social Research, 2023)
Research conducted by PR2Media at the end of 2022 found that 82.6% of 852 female journalists who were study respondents in 34 provinces reported having experienced sexual violence, including Central Java province. However, the research did not specifically discuss KBGO specifically for each region. In fact, digital violence targeting female journalists falls into the category of Online Gender-Based Violence (OGBV), namely acts of violence through internet technology to harass victims. The urgency of this research is to reveal Online Gender-Based Violence experienced by female journalists in Semarang as the capital of Central Java. The purpose of this study is to find out how the experience of OGBV that occurred during their profession, as well as to find out the types of OGBV that have been experienced. This research uses a qualitative method with data collection techniques through in-depth interviews, observations, surveys and literature studies, which are then described descriptively. The findings of this research show that the type of GBV experienced by female journalists in Semarang is cyber harassment (46.7), and the attitude taken by female journalists who are victims of online gender-based violence is to refuse to remain silent, an anomaly of Muted Group Theory